(untitled) (Interdisciplinary Studies Journal, 2021)
Law has as one of its premises the organization of society through norms, as well as the safeguarding of each citizen’s rights, ensuring that they are not violated by society, the State, or individuals and groups. In this understanding, it is known that society is constructed in a plural way, with the most diverse sexual and identity arrangements, which, as is known, are not always legally recognized and respected, with the Trans segment being daily victims of discrimination and violence. Therefore, this study uses bibliographic and procedural research as its methodology to analyze how (and if) trans women are viewed in the justice system during judicial proceedings, examining some developments and focusing on the times when they defend themselves and (if) they are heard. The analysis focuses on Case T in the municipality of Santo Ângelo, RS.